2013
DOI: 10.1016/j.bbagen.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A disintegrin and metalloproteinase-12 (ADAM12): Function, roles in disease progression, and clinical implications

Abstract: Background A disintegrin and metalloproteinase-12 (ADAM12) is a member of the greater ADAM family of enzymes: these are multifunctional, generally membrane-bound, zinc proteases for which there are forty genes known (21 of these appearing in humans). ADAM12 has been implicated in the pathogenesis of various cancers, liver fibrogenesis, hypertension, and asthma, and its elevation or decrease in human serum has been linked to these and other physiological/pathological conditions. Scope In this review, we begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 97 publications
(172 reference statements)
0
37
0
1
Order By: Relevance
“…ADAM12 exists in two alternatively spliced forms, a membrane-bound form (ADAM12L), with all ADAM typical structural domains; and a secreted form (ADAM12S) lacking the transmembrane and the cytoplasmic domain. 31 Discrete functions can be attributed to the individual ADAM12 domains. Both isoforms of ADAM12 are active proteases containing the catalytic domain of ADAM12 with the consensus HEXGHXXGXXHD zinc-binding motif,.…”
Section: Discussionmentioning
confidence: 99%
“…ADAM12 exists in two alternatively spliced forms, a membrane-bound form (ADAM12L), with all ADAM typical structural domains; and a secreted form (ADAM12S) lacking the transmembrane and the cytoplasmic domain. 31 Discrete functions can be attributed to the individual ADAM12 domains. Both isoforms of ADAM12 are active proteases containing the catalytic domain of ADAM12 with the consensus HEXGHXXGXXHD zinc-binding motif,.…”
Section: Discussionmentioning
confidence: 99%
“…The ADAMs, a family of MMPrelated metalloproteinases, are associated with cell adhesion, cell signaling, and proteolytic processing of a number of transmembrane proteins and play crucial roles in cancer progression and metastasis (28). ADAM12 is a member of this family and contributes to cancer progression and invasion through cleavage of various membrane-bound proteins (28,29) and high expression of ADAM12 has been reported in several cancer tissues such as brain (30), lung (31) and others. We have previously reported that ADAM12 promotes growth and metastasis of breast cancer (32) as well as of breast cancer risk (26) and that urinary levels of ADAM12 are predictive of disease status and stage in patients with breast cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…Conserved biological pathways between breast and ovarian cancer are known 44 , while some of the identified prognostic markers are also previously reported as cancer prognostic factors. CTSK expression is reported to govern breast tumor progression and prognosis by promoting extracellular matrix degradation and angiogenesis 45 ; CD53 expression was significantly associated with distant metastasis-free survival in ER − breast cancer patients 46 ; ADAM12 is proposed as a biomarker and drug target in breast cancer 47 . Significantly, although we identified two master regulators viz.…”
Section: Discussionmentioning
confidence: 99%